(3QSGdI aj GdEYQGHs
(3ChdgG (B:s
(3hHYO, agPg QSGdI def CQGO Cf jYde GdEYQGH aGdEYQGH Ydi KdGKI CbSGe Ydi GdCcKQ s
(3BNQgG (B:s
(3MjfFmP ef bHjd eG cGfJ hGbYI eG cGfJ NHQkG heaYhdkG hLhGHkG hMGdkG hJGHYkG (B((3NeSI(B) (3EdG Cf PcQ HPcQ GdCeKd Je s
(3Vef eLehY , JQJjHgG (B: (3ef U (B53 - (3U(B62s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B2 - (3U (B129 s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdfMhs